The impact of in‐person and video‐recorded animal experiences on zoo visitors' cognition, affect, empathic concern, and conservation intent. Issue 6 (13th August 2020) - Miller, Lance J.; Luebke, Jerry F.; Matiasek, Jennifer; Granger, Douglas A.; Razal, Catherine; Brooks, Heather J. B.; Maas, Kate
Abstract: Currently there are mixed results regarding the ability for media or more specifically video to increase a person's interest in conservation. However, there is a growing amount of evidence that in‐person experiences at a zoo or aquarium can increase a person's interest in conservation. The goal of the current study was to examine the difference between an in‐person experience viewing a polar bear training session and watching a video of the same experience on cognition, emotion, empathic concern, and conservation intent. A total of 124 Brookfield Zoo members were randomly assigned to one of three conditions. Condition 1 was an in‐person 10 min (Live Animal) experience viewing a training session with a polar bear. Condition 2 participants (Video Animal) watched a video of the same experience from Condition 1 and Condition 3 (Control) listened to the audio from Condition 1 but only viewed an image of one of our animal care specialists. Results suggest that the live condition is associated with higher probability of answering questions correctly, having a positive emotional experience, having greater empathic concern for wild bears, and wanting to get involved in conservation when compared to the control. These impacts were not observed for the video condition suggesting that for this study, watching a video of a training session was not an effective tool for getting people involved in conservation. Future research is needed to better understand this important topic, but we now have further evidence of the importance of in‐person zoo experiences. Abstract : Great Bear Wilderness classroom set up for the study. Highlights: Viewing a live training session of a polar bear impacted participants' knowledge, affect, empathic concern, and conservation intent when compared to a control. The same results were not observed for the video condition when compared to the control.